A Theory of Trade Policy under Dictatorship and Democratization - Benjamin Zissimos (Center for Economic Studies and ifo Institute (CESifo), 2017)
This paper develops a new model of trade policy under dictatorship and democratization. The paper makes two contributions. One is to provide a deeper understanding of the relationship between political institutions and economic efficiency by studying the endogenous interaction between the form of government and trade policy. The paper's second contribution is to show how a dictatorship can manipulate trade policy to maintain its grip on power in the face of permanent world price shocks, thus opening the door to a re-examination of trade policy re- sponses to technology shocks. The model is used to explain an interesting episode of trade policymaking between 1815 and 1846, during which time Britain substantially liberalized trade while Prussia, on the other side of the grain market, significantly increased protectionism.
Keywords: D30; D74; F11; F13; P16; 330; commitment problem; efficiency; fiscal capacity; institutions; trade policy